2004
DOI: 10.1007/s00415-004-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of anti-Jo-1-positive inflammatory myopathies

Abstract: The antisynthetase syndrome associated with anti-Jo-1-antibodies requires long-term immunosuppressive therapy in most patients. Whereas a complete clinical response of muscular symptoms is frequent, continued deterioration of the pulmonary system may occur despite immunosuppressive treatment, and may lead to fatal outcome. An interdisciplinary therapeutic approach is necessary for best possible results in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 21 publications
3
24
0
5
Order By: Relevance
“…5,8,10,11,13,17,19,21 Morbidity in both PM/DM and the anti-Jo-1 syndrome is related to acute respiratory decompensation at presentation and our study confirms this association and points out that the morphologic equivalent may be diffuse alveolar damage alone or acute lung injury superimposed on underlying fibrotic interstitial pneumonias such as usual interstitial pneumonia and fibrotic nonspecific interstitial pneumonia. 5,8,17,19,21 The limitations to this study are notable. First, this is a retrospective study, where clinical information, largely based on the referral nature of the patient population to the University of Pittsburgh, is potentially restricted.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…5,8,10,11,13,17,19,21 Morbidity in both PM/DM and the anti-Jo-1 syndrome is related to acute respiratory decompensation at presentation and our study confirms this association and points out that the morphologic equivalent may be diffuse alveolar damage alone or acute lung injury superimposed on underlying fibrotic interstitial pneumonias such as usual interstitial pneumonia and fibrotic nonspecific interstitial pneumonia. 5,8,17,19,21 The limitations to this study are notable. First, this is a retrospective study, where clinical information, largely based on the referral nature of the patient population to the University of Pittsburgh, is potentially restricted.…”
Section: Discussionsupporting
confidence: 79%
“…The most common of these is the antiJo-1 antisynthetase syndrome in which anti-histidyl tRNA synthetase (anti-Jo-1) antibodies are accompanied by clinical arthritis, Raynaud's phenomenon, myositis, mechanic's hands, and interstitial lung disease (ILD). [1][2][3][4][5][6][7][8][9][10] The anti-Jo-1 tRNA synthetase syndrome has a higher incidence of ILD, relative to classical PM/DM, approximating 90% in some series, and the presence of anti-Jo-1 antibodies correlates with poor patient prognosis. [11][12][13][14][15][16][17][18][19][20][21][22] In this report, we studied the pulmonary histopathologic changes of a select group of IIM patients with the anti-Jo-1 tRNA synthetase syndrome, generating the first and largest biopsy study focused on this specific group of patients.…”
mentioning
confidence: 99%
“…Moreover, certain causes require specific treatments. These treatments could be essential, as the long-term prognosis and the survival of patients with ASS, based on retrospective studies, showed a clear correlation with lung involvement [2,[18][19][20]. However, to date, the influence of cofactors associated with ILD, such as PH, has rarely been evaluated in large series.…”
Section: Introductionmentioning
confidence: 99%
“…4,31,33,34 Furthermore, positive anti-Jo-1 and/or interstitial pneumopathy as prognostic factors remain controversial. [34][35][36][37] In our patients, there was one death attributed to septic shock (hospital bronchopneumonia).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Since it is a rare syndrome, its prevalence in the general population is unknown. Moreover, ASS epidemiological studies [4][5][6] are scarce in the literature, except for a few case reports and serial cases. 3,[7][8][9][10][11] Therefore, we reported a cohort retrospective study of 18 patients with anti-Jo-1 ASS from our tertiary service.…”
Section: -3mentioning
confidence: 99%